Health sector solutions for promoting sustainable and nutritious diets - Guinto, Renzo R *; Baluyot, Christian Joseph; Gan, Connie C R; Ghosh, Upasona; Mahadzir, M Daniel A (BMJ Publishing Group, 2022)
Food is a critical foundation of human survival and a product of the Earth’s natural ecosystems and the human designed economic system. It is also a vital resource that is susceptible to social and environmental change, as shown by supply chain disruptions and price increases driven not only by the covid-19 pandemic and the war in Ukraine but by protracted crises in regions such as Africa, where massive food insecurities have been largely ignored for decades. These crises have shown that today’s global food system is far from resistant to shocks and stresses; its disturbance exacerbates already limited access, widens existing inequalities, and ultimately worsens nutritional status worldwide. In the backdrop is an evolving climate emergency that is already beginning to negatively affect food production, availability, affordability, and diversity across the globe. However, the damaging effects of climate change on nutrition and the food system are distributed unevenly, influenced by differentiated geographic and social vulnerabilities.